Jalan Tengah Konflik Agama Sains dalam Vaksinasi Covid-19 Perspektif Pemikiran Ian G. Barbour - Abd Hannan (LPPM IAIN Parepare, 2022)
This study examines the phenomenon of religious and scientific conflicts related to vaccination in the dynamics of handling Covid-19. There are two research problems in this study; How is the religion-science conflict related to the Covid-19 vaccine? How to mediate religion-science conflict in Covid-19 vaccination, from the perspective of Ian G. Barbour? Methodologically, this study uses qualitative research methods. There are two types of data in this study, namely primary data sourced from both print and online media in the period January 2020 to December 2022, and secondary data obtained from library sources. Using Ian G. Barbour's theory of the religion-science relationship, this study finds two important findings; First, one of the crucial problems in the midst of the efforts of many countries to fight the Covid-19 pandemic is the existence of conflict or friction between religious circles and scientists. The friction arose along with the differences in their mindset regarding the prevention and control of Covid-19, in this case the Covid-19 vaccination. In response to this polemic or conflict, it is necessary to have a breakthrough at the level of thought, namely by developing the idea of ​​a middle way, through which sages and clergy can meet, make peace, and compromise with each other. Second, in Iai G. Barbour's perspective, the relationship between religion and science can be mapped into four patterns, namely patterns of conflict, independence, dialogue, and finally the pattern of integration. Of these four patterns, the most ideal approach as a middle ground for religious and scientific conflicts related to Covid-19 vaccination is integration.